Epithelial-to-Mesenchymal Plasticity Harnesses Endocytic Circuitries - Corallino, Salvatore; Malabarba, Maria Grazia; Zobel, Martina; Di Fiore, Pier Paolo; Scita, Giorgio (Frontiers in Oncology, 2015)
The ability of cells to alter their phenotypic and morphological characteristics, known as cellular plasticity, is critical in embryonic development and adult tissue repair and contributes to the pathogenesis of diseases, such as organ fibrosis and cancer. The epithelial-to-mesenchymal transition (EMT) is a type of cellular plasticity. This transition involves genetic and epigenetic changes as well as alterations in protein expression and posttranslational modifications. These changes result in reduced cell-cell adhesion, enhanced cell adhesion to the extracellular matrix, and altered organization of the cytoskeleton and of cell polarity. Among them, loss of cell polarity represents the nearly invariable feature of EMT that precedes the other traits or might even occur in their absence. Time-resolved proteomic and phosphoproteomic analyses of cells undergoing EMT recently identified thousands of changes in proteins involved in many cellular processes, including cell proliferation and motility, DNA repair, and – unexpectedly – membrane trafficking. These results have highlighted a picture of great complexity. First the EMT transition is not an all-or-none response but rather a gradual process. Second EMT events are dynamic and frequently reversible, involving cell-autonomous and non-autonomous mechanisms. Endocytic circuitries have emerged as complex connectivity infrastructures for cellular networks required for the execution of different biological processes, with a primary role in the control of polarized functions. Thus, they may be relevant for controlling certain aspects of EMT. Here, by discussing a few paradigmatic cases, we will outline how endocytosis may be harnessed by the EMT process to promote dynamic changes in cellular identity, and to increase cellular flexibility and adaptation to microenvironmental cues, ultimately impacting on physiological and pathological processes